1997
DOI: 10.1135/cccc19970620
|View full text |Cite
|
Sign up to set email alerts
|

Polyfunctional Derivatives of Imidodiphosphoric Acid as Extractants

Abstract: The distribution of calcium, strontium, barium and scandium between aqueous and organic phases was studied using 0.1 M HNO3 or 0.01 to 0.1 M HCl as the aqueous phase and solutions of selected derivatives of organophosphoric reagents containing the conventional =P(O)NHP(O)= bifunctional group or the analogous trifunctional or tetrafunctional group in various organic solvents as the organic phase. The effect of substitution of one ester group by an OH or NH2 group was examined. While for the alkaline earth metal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…X-ray crystal structure analysis of TPh-OO [3] and TPh-SS [4,5] revealed that these compounds are formed in the crystal dimers via hydrogen bonds. Their very good solvation properties and some technological aspects were described earlier [4,6,7]. This work deals with the properties of the chelate-forming reagents specified above in the system aqueous phase -selected organic solvents.…”
Section: Introductionmentioning
confidence: 94%
“…X-ray crystal structure analysis of TPh-OO [3] and TPh-SS [4,5] revealed that these compounds are formed in the crystal dimers via hydrogen bonds. Their very good solvation properties and some technological aspects were described earlier [4,6,7]. This work deals with the properties of the chelate-forming reagents specified above in the system aqueous phase -selected organic solvents.…”
Section: Introductionmentioning
confidence: 94%
“…Some chlorofluoroalkane's solvents and CFC-112/B mixture were used as a highly inert, non-flammable and non-toxic organic phase. Their very good solvation properties and some technological aspects were described earlier [4,6,7].…”
Section: Introductionmentioning
confidence: 99%
“…To date, a lot of extractants have been developed and their extraction properties have been evaluated for a variety of metal ions. [1][2][3][4][5][6][7][8][9][10][11] In a previous study, we have developed novel bi-functional organophosphorus extractants in which two phosphonic acids were introduced as functional groups in the molecular structure for the separation of rare earth metals. 12 The result indicated that extraction performance of bi-functional extractants is very sensitive to the molecular structure of the spacer which connects the two functional moieties.…”
mentioning
confidence: 99%